(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Let I be an ideal of a ring R with identity. We say that idempotents modulo I can be lifted if for every a ∈ R such that a2 – a ∈ I there exists an idempotent e ∈ R such that e – a ∈ I. In this review, we will discuss various results about lifting idempotents and characterization of rings in terms of this property.